Perbandingan Insentif Pajak Indonesia, Malaysia, dan Singapura dalam Kondisi Pandemi Covid-19 - Mufidah Azzahra; Muhammad Rheza Ramadhan (InFestasi, 2022)
COVID-19 pandemic which caused state revenues, especially tax revenues in Indonesia to be hampered. This is also experienced by Indonesia's neighboring countries, namely Malaysia and Singapore. Therefore, the governments of Indonesia, Malaysia, and Singapore overcome these problems by issuing fiscal policies including policies on tax incentives. This study aims to compare the tax incentives in Indonesia with Malaysia and Singapore during the COVID-19 pandemic. The data collection method used is descriptive research method in the form of literature study. The results of the study show that Indonesia, Malaysia, and Singapore have similarities and differences in terms of providing tax incentives. What the three countries have in common is that they have the same concern for the empowerment of Small Micro Business (SMEs) and individual income. Then the difference is seen in terms of the approach of the governments of the three countries in providing tax incentives. Singapore has a tax system that is already quite competitive and business-friendly, there will be no fundamental changes to Singapore's tax rates due to the COVID-19 pandemic. Indonesia and Malaysia, which pay attention to changes in rates from various sectors in providing tax incentives. Pandemi covid-19 yang menyebabkan penerimaan negara terutama penerimaan perpajakan di Indonesia terhambat. Hal tersebut juga dialami oleh negara tetangga Indonesia yaitu Malaysia dan Singapura. Maka dari itu, pemerintah Indonesia, Malaysia, dan Singapura mengatasi permasalahan tersebut dengan mengeluarkan kebijakan fiskal termasuk kebijakan mengenai insentif perpajakan. Penelitian ini bertujuan untuk mengetahui perbandingan insentif perpajakan di negara Indonesia dengan negara Malaysia dan Singapura dalam kondisi pandemi covid-19. Penelitian ini menunggunakan studi kepustakaan deskriptif. Hasil penelitian menunjukkan bahwa Indonesia, Malaysia, dan Singapura memiliki persamaan dan perbedaan pemberian insentif perpajakannya. Persamaan dari ketiga negara tersebut ialah memiliki perhatian yang sama akan pemberdayaan Usaha Kecil Mikro (UKM) dan penghasilan individu. Perbedaannya adalah terlihat dari segi pendekatan pemerintah ketiga negara tersebut dalam memberi insentif perpajakannya. Singapura memiliki sistem perpajakan yang sudah cukup kompetitif dan ramah bisnis. Tidak ada perubahan mendasar pada tarif perpajakan Indonesia dan Malaysia memperhatikan perubahan tarif dari berbagai kalangan sektor dalam memberikan insentif.